2020
DOI: 10.1186/s12889-020-09899-5
|View full text |Cite
|
Sign up to set email alerts
|

Educational differences in labor market marginalization among mature-aged working men: the contribution of early health behaviors, previous employment histories, and poor mental health

Abstract: Background Social inequalities in labor force participation are well established, but the causes of these inequalities are not fully understood. The present study aims to investigate the association between educational qualification and labor market marginalization (LMM) among mature-aged working men and to examine to what extent the association can be explained by risk factors over the life course. Method The study was based on a cohort of men born between 1949 and 1951 who were examined for Swedish military… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Adapted from previous research, LMM was defined using four different measures: long-term unemployed, precarious employment, long-term sickness absence, and disability pension ( 23 , 24 ). Long-term unemployment and precarious employment were defined in the same way as the exposure variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapted from previous research, LMM was defined using four different measures: long-term unemployed, precarious employment, long-term sickness absence, and disability pension ( 23 , 24 ). Long-term unemployment and precarious employment were defined in the same way as the exposure variables.…”
Section: Methodsmentioning
confidence: 99%
“…Unemployment, precarious employment, sickness absence, or receiving a disability pension can all be considered types of LMM as the individual is more distant from the labor force ( 23 , 24 ). However, research within this area is scarce; one Nordic study found a positive association between precarious employment and self-reported sickness absence in the general working-age population ( 25 ).…”
mentioning
confidence: 99%
“…Inequalities in terms of labor market participation have been described yet little has been known about the underlying causes of such inequality [11]. Thern et al attempted to describe, in the case of Sweden, how education affects employability for marginalized groups as well as non-marginalized groups at work.…”
Section: Disability and Employment In The Worldmentioning
confidence: 99%
“…bACkgrOund Workers with common mental disorders (CMDs) like depression are at higher risk of work disability and long-term and recurrent sickness absence, [1][2][3] indicating a lower likelihood of sustainable return to work (SRTW) for that segment of the working population. 4 Research on sick-listed workers with CMDs describes common barriers to RTW, such as job strain, comorbidity, previous sickness absence, higher age and low education, [5][6][7] while factors such as positive RTW expectation, self-efficacy, high work ability, job control, decision control, and higher education seemingly facilitate RTW.…”
mentioning
confidence: 99%